ON DANGEROUS HEAVY METALS / METALLOIDS IN SOILS - Yu. Vodianitsky (Бюллетень Почвенного института им. В.В. Докучаева, 2011)
According to the current ecotoxicological data of Dutch ecologists, hazardous heavy metals/metalloids in the soil form a number of: Se > Tl > Sb > Cd > V > Hg > Ni > Cu > Cr > As > Ba. This series differs greatly from a number of hazards of heavy elements, adopted in Russia in accordance with GOST 17.4.1.02-83, in which the danger of Pb, Zn, Co in soils is exaggerated, and V, Sb, Ba - underestimated. The list of hazardous elements in the soil should also include to be included in Tl, Cr. The content of heavy metals/metalloids in contaminated soils is studied very unevenly: better 11: Cu, Zn, Pb, Ni, Cd, Cr, As, Mn, Co, Hg, Se; the other 46 were studied much worse, although there are dangerous ones among them: Ba, V, Tl.In Russia, the information on the content of these elements in soils is not enough, and it is on them that the attention of soil scientists and ecologists should be focused.